A survey of Malaysian emergency personnel on family presence during resuscitation - Kean, Lim Chee (2010)
The practice of family presence (FP) during resuscitation is gaining a foothold in Western countries but still largely not encouraged by Asian health-care personnel (HCP). This study aims to provide a Malaysian data on HCPs opinions ofFP. A non-probability survey was conducted in emergency departments (EDs) of four hospitals around Malaysia. A questionnaire was designed based on previous similar surveys conducted in Singapore. It was edited by two emergency physicians and pre-test was conducted in HUSM to validate and test the reliability of the questionnaire. All HCPs in four hospitals were included in this study which ran from October until December 2009. A total of 273 replies were obtained of which one third were doctors and the rest paramedics. Mean age was 32 years and there were equal number of male and female participants. The HCPs had worked an average of7.5 years with 5.1 years in the ED. It was found that 27% of doctors were more agreeable to FP compared to paramedics (p=O.OOl). However 54% of doctors and 32.4% of paramedics agreed that relatives had a right to FP. 57.6% of doctors compares to 67.6% of paramedics would like to be present during their own relative's resuscitation. Among the reasons for not allowing FP were it would be traumatic experience to the family, medico-legal reasons, breach of patient's privacy, interfere with resuscitation process, overcrowding, increase stress to HCPs and prolonging resuscitation efforts. Advantages of FP identified were assuring the family everything had been done, facilitate mourning, strengthen family bond and allow for final rites. Logistic regression of variant showed that the odds of a doctor agreeing to FP was 2.86 that of a paramedic (p-value=0.002). In conclusion, it was found that Malaysian emergency HCPs do not agree to FP. Surveys of the public may help to assess their opinions and whether it disagree with HCPs opinions.